Rapid and effective enrichment of mononuclear cells from blood using acoustophoresis. Issue 1 (December 2017) - Urbansky, Anke; Ohlsson, Pelle; Lenshof, Andreas; Garofalo, Fabio; Scheding, Stefan; Laurell, Thomas
Abstract Effective separation methods for fractionating blood components are needed for numerous diagnostic and research applications. This paper presents the use of acoustophoresis, an ultrasound based microfluidic separation technology, for label-free, gentle and continuous separation of mononuclear cells (MNCs) from diluted whole blood. Red blood cells (RBCs) and MNCs behave similar in an acoustic standing wave field, compromising acoustic separation of MNC from RBC in standard buffer systems. However, by optimizing the buffer conditions and thereby changing the acoustophoretic mobility of the cells, we were able to enrich MNCs relative to RBCs by a factor of 2, 800 with MNC recoveries up to 88%. The acoustophoretic microchip can perform cell separation at a processing rate of more than 1 × 105 cells/s, corresponding to 5 µl/min undiluted whole blood equivalent. Thus, acoustophoresis can be easily integrated with further down-stream applications such as flow cytometry, making it a superior alternative to existing MNC isolation techniques.